2017
DOI: 10.1039/c6fo01397j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of collagen hydrolysates from silver carp (Hypophthalmichthys molitrix) skin on UV-induced photoaging in mice: molecular weight affects skin repair

Abstract: The use of collagen hydrolysates (CHs) as a nutraceutical agent in skin aging has gained increasing attention. Here, the effects of various doses and molecular weights of CH from silver carp skin on photoaging in mice were investigated. The ingestion of CH at 50, 100 and 200 mg per kg body weight led to a dose-dependent increase in the hydroxyproline, hyaluronic acid and moisture contents of the skin, but it had no significant effect on the mice body weight, or on the spleen or thymus index. Furthermore, inges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…In present study, 13‐month‐old Kunming mice, equivalent to 45 years old of human life , were employed to investigate the effect of CPs intake on cytokines in skin and blood. The CPs, used in the present study, has been demonstrated to have a stronger beneficial effect on the aging skin than other collagen hydrolysates (including gelatin and CPs with higher molecular weight) in our previous publication . The mice were administered with CPs for 2 months, equivalent to approximately 4.5 years of human life .…”
Section: Discussionmentioning
confidence: 99%
“…In present study, 13‐month‐old Kunming mice, equivalent to 45 years old of human life , were employed to investigate the effect of CPs intake on cytokines in skin and blood. The CPs, used in the present study, has been demonstrated to have a stronger beneficial effect on the aging skin than other collagen hydrolysates (including gelatin and CPs with higher molecular weight) in our previous publication . The mice were administered with CPs for 2 months, equivalent to approximately 4.5 years of human life .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the beneficial effects of CPs. For instance, CPs derived from fish skin were demonstrated to have several protective effects on skin photo-aging and wound healing, as they improved moisture retention and repaired endogenous collagen and elastin protein fibers (28)(29)(30)(31)(32). Therefore, CPs are considered a useful material for the development of cosmetics, pharmaceuticals and medical products.…”
Section: Introductionmentioning
confidence: 99%
“…Zague et al, 2018 reported that collagen peptides modulate the metabolism of extracellular matrix proteins by human dermal fibroblasts (in culture) that were derived from sun-protected and sun-exposed body sites [172]. Song et al, 2017 examined the effects of collagen hydrolysates from sliver carp skin on UV-induced photoaging in mice and found that LMW peptides exerted beneficial effects when compared to high molecular weight CHs on HA levels and moisture content of the skin [173]. B. Probiotics Lactic acid bacteria consist of 26 genera now, and play an essential role in the food industry in the manufacture of many fermented products (cheese, yogurt, fermented vegetables, etc.).…”
Section: ( D D D D )mentioning
confidence: 99%